ANALISIS FAKTOR INTERNAL DAN EKSTERNAL TERHADAP RENTABILITAS BANK SYARIAH DI INDONESIA - Fajar Mujaddid; Suci Wulandari (Universitas Muhammadiyah Prof Dr Hamka, 2017)
The aims of this research are to analyze the internal and external factors which affect the profitability of sharia banks in the period 2011-2015 per-quarter. This research using panel data regression method. The results show that the capital (CAR) has no effect on profitability (ROA), Inflation has no effect on profitability (ROA), Liquidity (FDR) has influence on profitability (ROA), while efficiency (BOPO), Non Performing Financing (NPF), and Gross Domestic Product (GDP) have a negative and significant effect on the profitability of sharia banks.